2018
DOI: 10.5811/westjem.2018.10.39677
|View full text |Cite
|
Sign up to set email alerts
|

Does Implementation of a Corporate Wellness Initiative Improve Burnout?

Abstract: IntroductionBurnout affects over 50% of all physicians. Nearly 70% of emergency physicians are affected, and it has been found to be as high as 76% in resident physicians overall. Previous wellness initiatives have yielded variable results; therefore, we looked for interventions that could potentially be effective at reversing this trend. We explored effective wellness programs originating from other industries. Our objective was to implement a corporate wellness program with previous evidence of success in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…47 Studies of resilience training in EM have shown mixed results. [48][49] While personal resilience is important to prevent burnout and PTSD, a recent systematic review and metaanalysis of programs to reduce burnout in physicians suggests that focusing on adaptations to the work environment are more effective than interventions that target individual providers. 50 Noben et al found that an intervention to improve mental health among hospital staff was cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…47 Studies of resilience training in EM have shown mixed results. [48][49] While personal resilience is important to prevent burnout and PTSD, a recent systematic review and metaanalysis of programs to reduce burnout in physicians suggests that focusing on adaptations to the work environment are more effective than interventions that target individual providers. 50 Noben et al found that an intervention to improve mental health among hospital staff was cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the Resident Wellness Consensus Summit published the outline of a proposed comprehensive wellness curriculum for emergency medicine residency programs [22,23]. Another group implemented a corporate-based wellness curriculum in their emergency medicine residency program, which received negative feedback from participants [24]. Finally, several medical schools have published curricula for teaching wellness skills to medical students [20,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly encountered wellness intervention (5 of 8) was a formal, classroom-based initiative. 15 , 16 , 18 , 20 , 22 Three of these studies described a year-long curriculum 16 , 18 , 22 and two described a single session. 15 , 20 All five provided a broad overview of wellness during residency training and attempted to address multiple facets including work-life balance, stress management, and burnout coping mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies used a variety of previously published measures with existing validity evidence to assess the impact of wellness interventions ( Table 2 ). Two studies used the MBI-HSS 18 , 22 ; one used the Perceived Wellness Scale 21 ; and one used a combination of the Brief Resident Wellness Profile and Short Form Health Survey (SF-8). 16 Many of the studies also used satisfaction surveys to assess participant reactions to the interventions, 15 20 and two used a combination of both.…”
Section: Resultsmentioning
confidence: 99%